Adverse Life Events and Perinatal Depression Among Young Pregnant and Postpartum Women - Friesen, Kira (Université d'Ottawa / University of Ottawa, 2016)
Background: Young childbearing women have an increased risk of experiencing perinatal depression when compared to adult childbearing women. Perinatal depression has been associated with adverse life events in the literature and conceptually, in frameworks such as the Lifecycle Approach to Risk Factors for Mental Disorders Model. Purpose: The purpose of this manuscript-based thesis was to (1) determine the prevalence of: (i) adverse life events that have been associated with depression and (ii) depressive symptoms among the young pregnant and parenting women who access specialized services in an urban centre in Ontario, Canada; (2) determine which adverse life events are predictive of depression during the perinatal period, in this population; and (3) examine the psychometric properties of the Edinburgh Postnatal Depression Scale (EPDS) for use in a population of young childbearing women who access specialized services in an urban centre in Ontario, Canada. Methods: A survey was conducted with 102 young women from two agencies that provide specialized services to young parents. The interviewer-administered questionnaire included demographic questions, the Edinburgh Postnatal Depression Scale, the Antenatal Psychosocial Health Assessment, the Centers for Epidemologic Studies Depression Scale, Brown’s Support Behaviour Inventory. Results: 31.4% of the sample screened positive for perinatal depression. The only adverse life events found to predict perinatal depression were satisfaction with support from ‘others’ and intimate partner violence. Another predictor was very young maternal age (14 – 17 years). The EPDS was found to be psychometrically sound when used in this population of young childbearing women. Conclusion: In this study of young childbearing women in Ontario, Canada, we found a high prevalence rate of perinatal depression and adverse life events. Furthermore, we identified specific factors that predict the development of perinatal depression in this group. Nurses can use these findings to help prioritize perinatal screening efforts to identify this condition early on in order to lessen the adversities related to perinatal depression.